STRATEGI PENGEMBANGAN KARYAWAN PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI SELATAN - Muzayyanah Jabani (MUAMALAH, 2014)
This Research entitle the Strategy of Human Resources Development of Regional Office, Department of Religion in Province Of South Sulawesi. The purpose of this research is to know the factors having an effect in increasing the performance of Regional office human resources of Religion Department Province of South Sulawesi and to know the strategy of what can be used in increasing the performance of due to employees development of at regional office of religion Department Province of South Sulawesi. Analysis Method used in this research is multiple regression analysis to know the variable influence–independent variable to variable dependent.Independent variable is this model that have influence to increase the performance of human resources is: education, skill, motivation, and salary variable anticipated can influence the make-up of human resource performance of regional office of Religion Department Province of South Sulawesi. Result of research indicate that at significant level 95% the four variables, knowledge, skill, motivate and salary by simultaneous have an effect on the significant in increasing of human resources performance of Regional Office Religion Department Province of South Sulawesi.Strategy which better be gone through by organizational party in development human resources to word better is if we like to improve the knowledge, through the education, if we like to uplift skill earn with the training, to motivate the human resources better pay attention to giving position promotion to competent human resources promoted, medium to develop the human resources seen is salary which they is accepted by is how organizational party pay attention to give the bonus to human resources